Multiphase production : pipeline transport, pumping and metering - Falcimaigne, J. (Editions Technip, 2008)
Annotation This book presents the fundamentals of multiphase production with regard to flow simulations in multiphase pipelines, multiphase pumping and multiphase metering. It gives a large range of information on approaches and technologies which can be used today. It is designed for engineers involved in field development, but also for petroleum engineering students.
Keywords: Multiphase flow -- Congresses.; Oil fields -- Production methods -- Congresses.; Gas fields -- Production methods -- Congresses.; elektronické knihy; electronic books